Definicja legalna sztucznego sposobu działania - Borszowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article analyzes the legal definition of an artificial mode of action. This is a legal defin-ition introduced in the anti-avoidance clause. The base determinant and the determinants of the implementation of this definition were distinguished. Then their fulfillment was assessed. This analysis gave grounds for formulating postulates to change some legal provisions. It concerns introducing new definitions that clarify some concepts.
Keywords: definicje legalne; określenia nieostre; sztuczny sposób działania